Nurse's managerial functions in the daily life of a hemotherapy service at a university hospital (Research, Society and Development, 2022)
Objectives: To know how the Nurse uses management functions in daily life in the Hemotherapy Service in a university hospital. Method: Descriptive study, with a qualitative approach, with the setting of a Hemotherapy Service of a University Hospital of the state public network. Data collection was carried out through a semi-structured interview and it was decided to treat the data using Bardin's content analysis. Results: After transcribing and analyzing the interviews, it was possible to identify the managerial functions that nurses perform on a daily basis so that their teams can fully care for patients. Final Considerations: the nurses, where this study took place, act in order to provide all the necessary support for the correct performance of the activities, acting: in the elaboration of the scales; in conducting training; in the management of inputs; in the management of possible conflicts; and in the adoption of actions aimed at motivating teams.